If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 = 3p + 11 + -2p Reorder the terms: -3 = 11 + 3p + -2p Combine like terms: 3p + -2p = 1p -3 = 11 + 1p Solving -3 = 11 + 1p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-1p' to each side of the equation. -3 + -1p = 11 + 1p + -1p Combine like terms: 1p + -1p = 0 -3 + -1p = 11 + 0 -3 + -1p = 11 Add '3' to each side of the equation. -3 + 3 + -1p = 11 + 3 Combine like terms: -3 + 3 = 0 0 + -1p = 11 + 3 -1p = 11 + 3 Combine like terms: 11 + 3 = 14 -1p = 14 Divide each side by '-1'. p = -14 Simplifying p = -14
| 6=-6p-10+7p | | a+3ab-4ab= | | 3x-5+9x=-15 | | 8x^3-49x^2+6x=0 | | -8+10=9x+17 | | 1+a+x^2=p | | -9=-6p-7+7p | | y-4=(x-7)(x-7) | | 3=-4.5+4y | | -9=5p-12-4p | | x+19=139 | | 22x=-12 | | 2=-4.5+4y | | -16=-5(8n+3) | | -6=-9p+14+10p | | 1=-4.5+4y | | 121b^2-100= | | 0=-4.5+4y | | 2x-19=1421 | | 27=6+8+c | | 10x+20/25x+20 | | 191=-3x+7(4x-12) | | -6=-5p-12+6p | | 2z-6-7=-30 | | -28n^2=-96-184n | | -176=7x+5(-3x-16) | | 4x+14=2894 | | -5x+2(-4x+6)=77 | | 8(x+6)-8=40 | | -22=-4 | | 28-8x=x | | 29=-4x-7(-2x-17) |